2019
DOI: 10.1093/nar/gkz091
|View full text |Cite
|
Sign up to set email alerts
|

Human H4 tail stimulates HIV-1 integration through binding to the carboxy-terminal domain of integrase

Abstract: The integration of the retroviral genome into the chromatin of the infected cell is catalysed by the integrase (IN)•viral DNA complex (intasome). This process requires functional association between the integration complex and the nucleosomes. Direct intasome/histone contacts have been reported to modulate the interaction between the integration complex and the target DNA (tDNA). Both prototype foamy virus (PFV) and HIV-1 integrases can directly bind histone amino-terminal tails. We have further investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…These data make histone tails good candidates for potential receptors of incoming intasomes. This idea is further supported by findings showing that retroviral IN can bind, via its CTD directly to histone tails (Benleulmi et al 2017;Mauro et al 2019;Maskell et al 2015). HIV-1 IN mutagenesis studies have shown that amino acid substitutions that affect IN binding to nucleosomes and histone tails also affect viral infectivity (Benleulmi et al 2017).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…These data make histone tails good candidates for potential receptors of incoming intasomes. This idea is further supported by findings showing that retroviral IN can bind, via its CTD directly to histone tails (Benleulmi et al 2017;Mauro et al 2019;Maskell et al 2015). HIV-1 IN mutagenesis studies have shown that amino acid substitutions that affect IN binding to nucleosomes and histone tails also affect viral infectivity (Benleulmi et al 2017).…”
Section: Introductionmentioning
confidence: 81%
“…To further investigate the effect of LEDGF/p75 on functional integration complexes and determine whether the LEDGF/p75-mediated increase in IN chromatin-binding was related to the nucleosomal features of chromosomes, we performed typical in vitro integration assays using biotinylated mononucleosomes (MNs) immobilized on streptavidin beads as previously performed (Benleulmi et al 2017;Mauro et al 2019). As shown in Figure 3A, LEDGF/p75 strongly stimulated HIV-1 IN activity on MNs, while integration onto naked DNA was only slightly improved in the presence of the cofactor.…”
Section: Ledgf/p75 Modulates the Efficiency But Not The Selectivity Omentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, HIV-1 virion packages around 250 molecules of integrase, which is far more than needed from the recent structures of lentiviral intasomes. Also, although the structure of the PFV intasome bound to a nucleosome afforded important information on the chromatin capture by retroviral intasomes, the requirement for histones might differs from genus to genus [83,84], highlighting the need for additional structures of intasomes bound to nucleosomes. Additionally, early chromatinisation of retroviral pre-integration complexes has emerged as a feature of two retroviral genera [85,86].…”
Section: Discussionmentioning
confidence: 99%